2016
DOI: 10.1002/ldr.2604
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Variations with Land Use along the Precipitation Gradient in the North–South Transect of the Loess Plateau

Abstract: Knowledge of soil moisture spatial variation with land use along the precipitation gradient is necessary to improve land management and guide restoration practice in the water‐limited Chinese Loess Plateau. This study selected 45 sampling points at 11 sites across the north–south transect of the Loess Plateau based on the precipitation gradient and land use. Results showed that the vertical profiles of soil moisture revealed large variations with the precipitation gradient changing, especially in the surface l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 57 publications
3
26
0
1
Order By: Relevance
“…On the other hand, the moisture in the upper soil layer (0-1.4 m) for the three plantations was not obviously lower than that in the control grassland (Figure 2), which was consistent with recent studies on the spatial variations of soil moisture under different land uses in the Loess Plateau [18]. Moisture in the upper soil layer might be more susceptible to additional hydro-geographical factors in contrast to the deep soil layer, such as rain throughfall, canopy interception, and soil evaporation [39].…”
Section: Negative Effects Of Afforestation On Vertical Soil Moisturesupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, the moisture in the upper soil layer (0-1.4 m) for the three plantations was not obviously lower than that in the control grassland (Figure 2), which was consistent with recent studies on the spatial variations of soil moisture under different land uses in the Loess Plateau [18]. Moisture in the upper soil layer might be more susceptible to additional hydro-geographical factors in contrast to the deep soil layer, such as rain throughfall, canopy interception, and soil evaporation [39].…”
Section: Negative Effects Of Afforestation On Vertical Soil Moisturesupporting
confidence: 91%
“…The results of redundancy analyses indicated that afforested vegetation types had a weak influence on the degree of soil moisture decline following afforestation (Figure 3). Comparisons of soil moisture under different land uses has been well investigated [7,18,45]. However, such species-dependent impacts on the degree of soil moisture alterations following afforestation across a precipitation gradient has rarely been explored previously.…”
Section: Controls Of Afforested Vegetation Types and Precipitation Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Grasslands are one of the largest ecosystems in the world and play an important role in vegetation restoration (Zhang, Zhao, Liu, Fang, & Feng, 2016). Besides, recent studies have suggested that grasslands have higher values of soil water content (SWC), whereas scrublands and forests present drier conditions at deeper soil layers in dry lands (Wang, Wang, Fu, Yang, & Li, 2017). Precipitation is the sole source of soil water replenishment in arid and semiarid regions; improper planting patterns can aggravate water scarcity and strongly influence the growth and natural succession of vegetation (Porporato, D'odorico, Laio, Ridolfi, & Rodriguez-Iturbe, 2002;Wilcox & Newman, 2005;Shangguan & Zheng, 2006;Chen et al, 2008;Feng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…式中:SMi和 [37] 。一般认为,降水是干旱、半干 旱地区土壤水分补充的主要来源,在较大的尺度上与蒸散发共同控制着土壤水分含量及 其时空动态格局 [38][39] 。黄土高原具有典型的大陆性季风气候,水分输送受距离、地形、地 貌的影响,降水自东南向西北递减,这种降水格局控制着多数生态过程 [40] 。受降水梯度 影响,本研究中草地 0~3 m 各层土壤水分自东南向西北均呈相应递减趋势 (图 1、图 3) 。各个土层土壤水分与年均降水量均呈极显著正相关 (P<0.01) ,说明区域尺度上 0~3 m 土壤水分空间异质性主要受降水格局主导 [41] 。此外,本研究中土壤水分和年均降水量 的相关系数在浅层 (0~1 m) 最大,随着深度的增加而减小,这是由于黄土高原地区地 下水埋藏深,使得天然降水成为土壤水分补给的唯一来源,降水对土壤水分的补充随着 土层深度的增加而减少 [42] 。 在水分限制地区,陆地生态系统对气候变化的敏感性很大程度上源于降水时空格局 的变化 [4] 。降水减少不仅可以直接降低土壤有效水分,还可以限制根际微生物的正常活 动,进而影响植物对水分、养分的吸收、运输和利用 [43] 。在黄土高原地区,降水格局通 过调控中生、旱生草本种类、多度和高度,进而影响群落的分布、结构和生态功能 [7,23] 。 图 4 物种多样性与年均降水量之间的关系 Key words: soil moisture; species diversity; precipitation gradient; tradeoff analysis; Loess Plateau…”
unclassified